Exploratory teaching of geometry using dynamic geometry software and learning of mathematics teachers: A systematic review - Gutiérrez-Araujo, Rafael Enrique (2023)
[Objective] This article analyzes the literature related to research on continuing training processes of mathematics teachers, whose objectives are teacher learning, the study of exploratory teaching, or the links between the use of dynamic geometry software (DGS) and professional education. [Methodology] A meta-ethnography of 18 studies published in the period 2001-2021, encountered through searches in databases and mathematics education journals, was carried out. The analysis consisted of three stages: interpretative syntheses of each study; integrative syntheses, based on the recognition of convergences and divergences; and a final synthesis. [Results] In general terms, the review revealed that: (a) the predominant conception of teacher learning is related to participation of teachers in communities of practice; (b) exploratory teaching is compatible with the use of DGS, and its promotion in educational processes usually takes into account the interaction between theoretical and practical activities; and (c) teachers who begin to incorporate DGS into classroom activities may fail to take full advantage of the potential of this instrument for teaching, due to the emergence of unexpected situations during the class, or because of their convictions about the pedagogical use of digital technologies. [Conclusions] Among the most important conclusions, it is clear that incorporation of DGS in the classroom can be successfully achieved through teachers’ progressive and critical awareness of the pedagogical knowledge that supports exploratory teaching as an educational practice.